1988
DOI: 10.1007/bf02571311
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of anisotropic vertebral trabecular bone loss during aging by quantitative image analysis

Abstract: Age-dependent variations in the architecture of vertebral trabeculae in both the vertical and horizontal planes were characterized by quantitative image analysis. Images were obtained from autopsy specimens of the third lumbar vertebrae in 61 subjects (30 men and 31 women) whose ages ranged between 33 and 89 years). All subjects had died acutely either after trauma or illnesses unrelated to the skeleton. Using mathematical morphology techniques, we measured total bone area and perimeter, and the width of trabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(42 citation statements)
references
References 18 publications
6
36
0
Order By: Relevance
“…Increased Tb.Sp implies a decrease in Tb.N, which was found in earlier studies where shortening or complete loss of trabeculae was documented [18,28]. In another study, it was found that the Tb.N decreased significantly with age for both horizontal and vertical trabeculae [27].…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Increased Tb.Sp implies a decrease in Tb.N, which was found in earlier studies where shortening or complete loss of trabeculae was documented [18,28]. In another study, it was found that the Tb.N decreased significantly with age for both horizontal and vertical trabeculae [27].…”
Section: Discussionsupporting
confidence: 58%
“…Opposed to Tb.Sp, Tb.Th is of higher controversy and has thoroughly been investigated by means of two-dimensional (2-D) and 3-D methods. In some studies, it was found that the mean Tb.Th decreased significantly with age either in all trabeculae [28][29][30] or in horizontal trabeculae only [25,27] whereas in other studies, no significant decrease could be observed [12,22]. Other studies even speculated that vertical elements that are subjected to compression could increase in thickness as a compensatory response to loss of horizontal trabeculae [24,63].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Reductions in trabecular volume, number, and width have been well documented in specimens of older bone [13,14]. These alterations are due to a variety of factors, including Chan/Duque changes in gonadal status, nutrition, and physical activity.…”
Section: Differences In Aged Bonementioning
confidence: 99%
“…For trabecular bone, the number and thickness of the trabeculae are decreased, and the size of the intertrabecular spaces increase (113)(114)(115)(116). As transverse struts of the trabecular become thinner and fail, the anisotropy increases with age (112,117), and the longitudinal struts become more likely to buckle (118).…”
Section: Mechanical Behaviour Of Trabecular Bonementioning
confidence: 99%